Farmers’ Practices in Using Insecticides to Control Spodoptera exigua Infesting Shallot Allium cepa var. aggregatum in the Shallot Production Centers of Java - Gracia Melsiana Aldini; Y. Andi Trisyono; Arman Wijonarko; Witjaksono Witjaksono; Herman de Putter (Jurnal Perlindungan Tanaman Indonesia, 2020)
The beet armyworm, Spodoptera exigua Hübn. (Lepidoptera: Noctuidae) is a major insect pest of shallot in Java. This research was aimed to determine how insecticides were used as the common farmers practice  for controlling S. exigua. The research was conducted in three shallot production centers in Java: the Districts of Brebes (Central Java Province), Nganjuk (East Java Province), and Bantul (the Special Region of Yogyakarta).  Surveys were conducted by interviewing thirty shallot farmers as respondents from each district. The selected thirty farmers were taken from  four sub-districts. Almost all farmers (93.3%) in the three districts had similar perception that S. exigua was the major insect pest in shallot and 84.4% farmers stated that this insect was difficult to control. The four most common insecticides active ingredients  used were chlorfenapyr, methomyl, chlorpyrifos, and emamectin benzoate. Insecticides remained the first choice and they were applied throughout the shallot season mostly based on the calendar (1-3 days interval). When using insecticides farmers tend to exceed the label recommended rates, and the farmers mostly mixed different insecticides into one spray solution. These results suggest that application of insecticides to control S. exigua was already exessive. The potential risks and efforts essential to minimize the risks are discussed.